Assessing Final Year Engineering Projects : Ensuring Learning and Teaching Standards and AQF8 Outcomes : Final Report. - Rasul, Mohammad; Lawson, Justine; Howard, Prue; Martin, Fae; Hadgraft, Roger; Jarman, Rob; Kestell, Colin; Anwar, Faisal; Stojcevski, Alex; Henderson, Alan; Kootsookos, Alex (Office for Learning and Teaching, 2015)
Engineering schools in Australia are facing several urgent challenges, making sure that: 1. the requirements of the FYEPs meet the AQF8 definition of research outcomes 2. the FYEPs provides adequate evidence of threshold learning outcomes for engineering 3. assessment practices are reliable and valid 4. industry perceptions are adequately addressed, because these capstone experiences often open employment doors for graduates. This project proposes the development of tools and processes to ensure the required quality outcomes in these major areas: 1. Tools to evaluate how well students can apply much of the knowledge gained during their university studies in solving a real life problem (i.e. a good practice guideline for assessment of FYEPs based on the threshold learning outcomes for engineering); 2. Clear definition of educational purposes and expectations of FYEP, particularly in the key area of research skills (AQF8); 3. Benchmarking of these outcomes based assessment practices with industry partners and with stage 1 competency standards of engineers Australia.